Faktor - Faktor Yang Mempengaruhi Implementasi Kebijakan Pengajuan Cuti Pegawai Pada Masa Pandemi Covid-19 Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Provinsi Sumatera Selatan - Ekawarni, Riniarti Dian; Sulastri, Sri; Febrianza, Muhammad (@-Publik: Jurnal Administrasi Publik, 2021)
Annual leave can be filed once a year for 12 working days. The rules for officer leave are found in the National Civil Service Regulations number 24 of 2017 concerning Procedures for Giving Civil Servant Leave Civil, however, in its implementation during the Covid-19 Pandemic employees are expected to postpone their annual leave, especially when it coincides with cancellation of joint leave. The results of the study show that the Implementation of the policy for applying form employee leave is carried out according to the SOP, which 1-2 working days,and processed internally. By general implementation of submission policy officer leave at the time of the Covid-19 Pandemic at the investment Departement and one stop integrated service office this study uses qualitative research methods in the form of written data explained orally by the respondents observed.